2019
DOI: 10.11604/pamj.2019.33.91.17000
|View full text |Cite
|
Sign up to set email alerts
|

Intradialysis blood pressure changes among chronic kidney disease patients on maintenance haemodialysis in a tertiary hospital south - south Nigeria: a 2 year retrospective study

Abstract: Introduction Haemodialysis (HD) which is a form of renal replacement therapy commonly prescribed for patients with chronic kidney disease (CKD). However, it is not without deleterious haemodynamic responses which may occur either during or immediately after the termination of the procedure. These may include hypotension or hypertension. Methods This was a retrospective study that reviewed chronic kidney disease (CKD) patients on maintenance haemodialysis at the renal un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…The diminished glomerular filtration (the initiating stage of urine formation) cause increased inter dialytic weight gain (from excessive fluid retention) and this is commonly managed with large volume ultrafiltration which can precipitate IDH. 27 The use of erythropoiesis stimulating agents (ESAs) increased the risk for IDHT, similar to findings by Wilson et al that linked the use of ESAs with hypertension, hyperviscousity and thrombus formation. 28 The positive correlation between BMI and IDHT in this study, mirrors findings by Shu-Zhong.…”
Section: Discussionsupporting
confidence: 55%
“…The diminished glomerular filtration (the initiating stage of urine formation) cause increased inter dialytic weight gain (from excessive fluid retention) and this is commonly managed with large volume ultrafiltration which can precipitate IDH. 27 The use of erythropoiesis stimulating agents (ESAs) increased the risk for IDHT, similar to findings by Wilson et al that linked the use of ESAs with hypertension, hyperviscousity and thrombus formation. 28 The positive correlation between BMI and IDHT in this study, mirrors findings by Shu-Zhong.…”
Section: Discussionsupporting
confidence: 55%
“…Cameroon, which had found age as a factor associated with the occurrence of DHBP. Which would be at odds with those found by Okpa and Col. Nigeria [15], Labarcon and Bad-ang in the Philippines [11], and Van Buren and Col. Texas who had not found a statistically significant link. This finding could be explained in our series by the youngness of the Guinean population, but also by the shorter life expectancy of our population, which is 60.62 [16] years.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with DHBP, men were the most represented 66.0% (n-35) versus 33.9% (n-18) of women, or a sex ratio of 1.9 in favour of men (Text). This result is consistent with those found by Labarcon and Bad-ang in the Philippines [11] in 2015, Sebastian and Col. in South Africa in 2016 [13] and Okpa and Col. Nigeria in 2019 [15] who reported male predominance with a sex ratio of 1.1; 1.2 and 1.2 respectively. Our results are identical to those reported by Moustapha and collar.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of symptomatic IDH falls within the very wide range reported in previous studies, but higher than the 10.1% reported by Kuipers et al 44 for the EBPG, and lower than the 31.3% found in a study in Nigeria. 6 The lower rate in the EBPG compared to this study is expected, considering the association of several limiting factors in LINs that would normally entail higher rates of dialysis complications like IDH. One would have expected a higher rate compared to findings by Okpa and his group, 6 since intradialysis hypertension was excluded in this study, but the subjective nature of symptom reportage and perhaps the acceptance of these by the dialysis team could differ widely between centres.…”
Section: Discussionmentioning
confidence: 56%
“…[3][4][5] In the authors' local environment, the prevalence of IDH is reported to be 31.3% and 19.4% using the NKF-KDOQI criteria, and 8.6% using the European Best Practices Guidelines (EBPG). [6][7][8] The absence of a consensus definition has limited the scope of research on IDH and its outcome. However, Flythe et al 10 reported that the nadir BP was more predictive of future mortality of the eight IDH definitions they reviewed.…”
Section: Introductionmentioning
confidence: 99%